Confronting Budget Deficits. (Economic Issues; Economic Issues ;, 1996)
The phenomenon of substantial peacetime budget deficits over the past20 years has been traced to the burden of entitlements, a slowdown ineconomic productivity, and demographic and macroeconomic shifts in theindustrial countries. Though smaller and structurally different, deficitsin developing countries have also become worrisome. Most economists agreethat measures to reduce government spending are imperative, particularlythrough restructuring entitlement programs.